The presence of gasping predicts long-term survival in out-of-hospital cardiac arrest patients - Knor, Jiri; Seblova, Jana; Skulec, Roman; Seblova, Dominika; Malek, Jiri (Biomedical papers, 2018)
Background: The presence of gasping in out-of-hospital cardiac arrest (OHCA) patients predicts short-term prognosis. We performed a retrospective study to evaluate whether the presence of gasping at the time of Emergency Medical Service (EMS) arrival in the case OHCA patients of presumed cardian origin has any impact on six-month survival and/or sustained return of spontaneous circulation (ROSC). Methods: We collected and analyzed Utstein Style data for all patients resuscitated for OHCA of presumed cardiac origin by the EMS of the Central Bohemian Region from July 1st, 2013 to June 30th, 2014. Results: During the data collection period, 565 cases of OHCA of presumed cardiac origin were reported. Gasping at the time of EMS arrival was identified in 23.9%. The presence of gasping was associated with a significantly increased frequency of sustained ROSC (48.1 versus 20.7%, P<0.001) and six-month survival (40.7 versus 16.7%, P<0.001) than in non-breathing patients. Presence of gasping upon EMS arrival has been found to be an independent positive predictor of sustained ROSC (OR 2.51, CI 95% 1.59-3.98, P<0.001). The occurrence of gasping at the time of EMS arrival at the scene was significantly related to response time from EMS activation to arrival. Conclusion: The presence of gasping upon arrival of the EMS for the patient with OHCA of presumed cardiac origin predicts both improves short-term and long-term prognoses.
Keywords: gasping; out-of-hospital cardiac arrest; return of spontaneous circulation; long-term survival